Penerapan Keselamatan dan Kesehatan Kerja (K3) di Area Finishing-1 PT. Indah Kiat Pulp and Paper, Tbk. Perawang - Sari, Resy Kumala; Hasanah, Hijratul; Adeswastoto, Hanantatur (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
High quality products and maintain their existence. Human resources are an investment for companies to increase productivity, because this era of globalization is accompanied by tight, heavy and fast competition, so all aspects require accurate calculations. The research method used in this research is a qualitative descriptive research method. Based on observations made in the finishing area-1, it is necessary to evaluate or formulate a policy for implementing occupational safety and health in the finishing area-1. Because there are still some employees and work partners who ignore occupational safety and health in the work environment. PT. Indah Kiat Pulp & Paper has implemented occupational health and safety protection for employees and work partners in the company, but there are several employees and work partners who experience work accidents while doing work which is caused by several factors, namely environmental factors and human factors. The most important factor is the human factor, there is an element of negligence on the part of the workers themselves because they do not heed instructions from the boss/employer in the employee sector and their work partners. Implementation of occupational health and safety protection for PT finishing area-1 workers. Indah Kiat Pulp & Paper Perawang has done quite well, by implementing programs such as working environment conditions, identifying hazards, knowing potential hazards, implementing a work safety system and preparing K3 Implementation Facilities and Infrastructure.